A Draft Genome Assembly of Culex pipiens pallens (Diptera: Culicidae) Using PacBio Sequencing. (27th January 2021) - Peng, Cheng; Qian, Zhang; Xinyu, Zhang; Qianqian, Le; Maoqing, Gong; Zhong, Zhang; Ruiling, Zhang
Abstract: The Northern house mosquito, Culex pipiens pallens, serves as important temperate vectors of several diseases, particularly the epidemic encephalitis and lymphatic filariasis. Reference genome of the Cx. pipiens pallens is helpful to understand its genomic basis underlying the complexity of mosquito biology. Using 142 Gb (∼250×) of the PacBio long reads, we assembled a draft genome of 567.56 Mb. The assembly includes 1, 714 contigs with a N50 length of 0.84 Mb and a Benchmarking Universal Single-Copy Orthologs (BUSCO) completeness of 95.6% ( n  = 1, 367). We masked 60.63% (344.11 Mb) of the genome as repetitive elements and identified 2, 032 noncoding RNAs. A total of 18, 122 protein-coding genes captured a 94.1% of BUSCO gene set. Gene family evolution and function enrichment analyses revealed that significantly expanded gene families mainly involved in immunity, gustatory and olfactory chemosensation, and DNA replication/repair.